Impact assessment of investment motivation toward mutual funds - Ghimire, Dinesh Mani; Adhikari, Madhav (Journal of Emerging Management Studies, 2023)
Purpose - The purpose of this study is to assess the impact of investment motivation on mutual fund investment decisions by Nepalese investors. The research seeks to identify the key drivers that influence Nepalese investors’ decisions in this context. Design/methodology/approach - The research design employed in this study was a descriptive and causal comparative research. The primary data was gathered from individual investors who were actively involved in trading on the Nepal Stock Exchange (NEPSE). To assess respondents’ perceptions and factors influencing investment alternatives, a structured questionnaire survey was used. The sample size consisted of 384 participants, and they were selected through judgmental sampling technique. Findings and Conclusion - The research findings revealed that while there was a growing interest in mutual fund investments among Nepalese investors, there was a lack of awareness and understanding about these investment vehicles. The paper found that investor awareness level, fund manager qualities, risk perceptions, and fund performance positively affected mutual fund investment decisions in Nepal. These factors played an important role in determining investors’ preferences and choices. The regression model demonstrated a good fit for the data, explaining 55.8% of the variation in investment decisions. The study also emphasized the significance of effective selection and monitoring processes for mutual fund schemes, including evaluating fund managers’ performance and assessing the risk-return profile of different options. Implications - The findings implied the need for transparent reporting practices, access to reliable performance data, and investor-friendly policies. Policymakers should streamline regulations and create a favorable environment for mutual fund investments. These implications can contribute to the overall development of the capital market in Nepal by attracting more investors and fostering investor confidence in mutual fund schemes.